Post-mortem Examination of the Nervous System: Fresh versus Fixed. (22nd July 2022) - Hammond, Robert; Dunham, Chris; McFadden, Deborah; Del Bigio, Marc; Perez-Rosendahl, Mari; Vinters, Harry V.
ABSTRACT: Background: Post-mortem examination of the nervous system is a complex task that culminates in "brain cutting". It relies on expertise in neuroanatomy, clinical neurosciences, neuroimaging and experience in order to recognise the most subtle abnormalities. Like any specialist examination in medicine, it warrants formal training, a standardised approach and optimal conditions. Revelations of aberrant tissue retention practices of a select few pathologists (e.g. Goudge, Liverpool and Alder Hey inquiries) and a motivated sociopolitical climate led some Canadian jurisdictions to impose broad restrictions on tissue retention. This raised concerns that nervous system examinations for diagnosis, education and research were at risk by limiting examinations to the fresh or incompletely fixed state. Professional experience indicates that cutting an unfixed or partly fixed brain is inferior. Methods: To add objectivity and further insight we sought the expert opinion of a group of qualified specialists. Canadian neuropathologists were surveyed for their opinion on the relative merits of examining brains in the fresh or fully fixed state. Results: A total of 14 out of 46 Canadian neuropathologists responded (30%). In the pervasive opinion of respondents, cutting and sampling a brain prior to full fixation leads to a loss of diagnostic accuracy, biosafety and academic deliverables. Conclusions: Brain cutting in the fresh state is significantly impaired along multiple dimensions of relevance to a pathologist's professional roles and obligations.